(untitled) (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2013)
Cephalometric radiography is the most significant tool for improving taxonomy, communication and analysis of dentofacial variation, as in orthodontic evaluation and treatment, analysis of craniofacial morphology is essential. Steiner’s analysis was used in this study; because its methods of assessing skeletal and dental morphology are very useful and valid providing maximal clinical information with the least number of measurements. The objective of this study was to describe the craniofacial pattern of Bangladeshi young adults and to compare it with accepted standards for the Caucasian population according to Steiner analysis. The study will also evaluate morphological differences between male and female Bangladeshi normal occlusion subjects. This is a cross-sectional observational study having both descriptive and analytical components. The study was conducted in Dhaka Dental College and Hospital on 52 Bangladeshi young adults (27male and 25 females), aged 21-27 years, having balanced harmonious facial profiles, clinically acceptable occlusion with permanent dentition and no history of orthodontic treatment. Lateral cephalometric radiographs of these subjects were used for a series of cephalometric analyses. All the measurements were computed statistically. The study findings show that Bangladeshi subjects were more protrusive skeletally and dentally than Caucasians with a greater tendency towards bimaxillary protrusion. Furthermore, the mandibular plane angle was smaller than that of the Caucasians, suggesting more prominent horizontal growth pattern in the Bangladeshis. However, when the male and female Bangladeshi subjects were compared, no significant differences were found in cephalometric craniofacial parameters between both sexes. In view of the findings of this study, it is evident that there are some fundamental differences in the craniofacial structure between Bangladeshis and the Caucasians. These differences should be kept in mind to facilitate better diagnosis, and orthodontic treatment for Bangladeshi patients. The results of the present study support the idea that a single standard of facial esthetics should not be applied to all racial and ethnic groups. DOI: http://dx.doi.org/10.3329/bjodfo.v2i1.15997 Ban J Orthod & Dentofac Orthop, October 2011; Vol-2, No.1, 11-15